APPLYING SAS (SYNTHETIC ANALITICAL STRUCTURE) METHOD IN IMPROVING INITIAL READING SKILLS AT GRADE I SD NEGERI 81 PEKANBARU - Yusmiati (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2021)
This research was a classroom action research conducted at SD Negeri 81 Pekanbaru. The subjects of this study were 30 grade I students at SDN 81 Pekanbaru. Required learning tools such as a syllabus, lesson plans, and worksheets were prepared before conducting the research. In addition, evaluation questions and daily tests were also designed by the researcher. The initial data of the average score of students’ learning outcomes was 58.03. Then, SAS (Synthetic Analytical Structure) method was applied in cycle I in order to improve the initial reading skills, and the average score in cycle I was 69.17; in other words, it increased for as many as 11.14. Furthermore, the average score in cycle II became 77.30 or increased for 8.13. This implied that SAS method increased students’ activity in which at the first meeting in cycle I, the percentage of students’ activity was 40% while the percentage of the second meeting was 50%. Then, the percentage of students’ activities at the third meeting in cycle II was 60%, and it increased to 75% at the fourth meeting in cycle II. In addition, SAS learning method also increased teachers’ activity in which the percentage of teachers’ activities at the first meeting in cycle I was 45% while the percentage of teachers’ activities at the second meeting was 60%. Moreover, the percentage of teachers’ activities at the third meeting in cycle II was 70%. Finally, the teachers’ activities at the fourth meeting in cycle II increased to 75%. Thus, it could be concluded that SAS (Synthetic Analytical Structure) learning method improved the initial reading skills of grade I students at SD Negeri 81 Pekanbaru for the academic year 2018/2019.This research was a classroom action research conducted at SD Negeri 81 Pekanbaru. The subjects of this study were 30 grade I students at SDN 81 Pekanbaru. Required learning tools such as a syllabus, lesson plans, and worksheets were prepared before conducting the research. In addition, evaluation questions and daily tests were also designed by the researcher. The initial data of the average score of students’ learning outcomes was 58.03. Then, SAS (Synthetic Analytical Structure) method was applied in cycle I in order to improve the initial reading skills, and the average score in cycle I was 69.17; in other words, it increased for as many as 11.14. Furthermore, the average score in cycle II became 77.30 or increased for 8.13. This implied that SAS method increased students’ activity in which at the first meeting in cycle I, the percentage of students’ activity was 40% while the percentage of the second meeting was 50%. Then, the percentage of students’ activities at the third meeting in cycle II was 60%, and it increased to 75% at the fourth meeting in cycle II. In addition, SAS learning method also increased teachers’ activity in which the percentage of teachers’ activities at the first meeting in cycle I was 45% while the percentage of teachers’ activities at the second meeting was 60%. Moreover, the percentage of teachers’ activities at the third meeting in cycle II was 70%. Finally, the teachers’ activities at the fourth meeting in cycle II increased to 75%. Thus, it could be concluded that SAS (Synthetic Analytical Structure) learning method improved the initial reading skills of grade I students at SD Negeri 81 Pekanbaru for the academic year 2018/2019.